The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.7554/elife.27311
|View full text |Cite
|
Sign up to set email alerts
|

The structure of a LAIR1-containing human antibody reveals a novel mechanism of antigen recognition

Abstract: Antibodies are critical components of the human adaptive immune system, providing versatile scaffolds to display diverse antigen-binding surfaces. Nevertheless, most antibodies have similar architectures, with the variable immunoglobulin domains of the heavy and light chain each providing three hypervariable loops, which are varied to generate diversity. The recent identification of a novel class of antibody in humans from malaria endemic regions of Africa was therefore surprising as one hypervariable loop con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 32 publications
(56 reference statements)
0
20
0
Order By: Relevance
“…Mass spectrometry identified the target antigens for LAIR1 as belonging to members of the repetitive interspersed families of polypeptides (RIFIN) family -the largest family of P. falciparum antigens displayed on infected erythrocytes 9 . Furthermore, X-ray crystallography analyses 11 revealed that LAIR1 is well folded and is displayed on the tip of V region in an appropriate configuration for interaction with antigen (FIG. 1A).…”
Section: [H2] Non-ig V Region Insertionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mass spectrometry identified the target antigens for LAIR1 as belonging to members of the repetitive interspersed families of polypeptides (RIFIN) family -the largest family of P. falciparum antigens displayed on infected erythrocytes 9 . Furthermore, X-ray crystallography analyses 11 revealed that LAIR1 is well folded and is displayed on the tip of V region in an appropriate configuration for interaction with antigen (FIG. 1A).…”
Section: [H2] Non-ig V Region Insertionsmentioning
confidence: 99%
“…The antigens are presented as shapes in dark blue. Right panels: side and top views of the structural representations of antibody MGD21 with LAIR1 insertion and of the broadly neutralizing HIV-1 antibody 3BNC60 with indel (created using PDB file 5NST 11 , and 3RPI 117 , respectively). The structural models were visualized by UCSF Chimera software package 118 .…”
Section: Box 2 Conventional Mechanisms For Antibody Diversificationmentioning
confidence: 99%
“…In the causative agent of the most deadly human malaria, Plasmodium falciparum, RIFINs form the largest erythrocyte surface protein family 1 . Some RIFINs can bind inhibitory immune receptors, acting as targets for unusual antibodies containing a LAIR1 ectodomain 2 - 4 , or as ligands for LILRB1 5 . RIFINs stimulate LILRB1 activation and signalling5, thereby potentially dampening human immune responses.…”
mentioning
confidence: 99%
“…However, for peptides whose "active" structure (i.e., target-bound state) assume lasso-like conformation, loop-insertion often allows functional fusion 23,30 . In fact, such "binding-domain insertion" has been found in several natural antibodies where target-binding is mediated by small (~30 residues) to large (~100 residues) domain inserted at the tip of CDR3 loop 31,32 .…”
Section: Discussionmentioning
confidence: 99%